Legal Perspectives on Passampo Siri’ Marriage and Determination of Biological Father's Status in Sidenreng Rappang Regency - Basri, Rusdaya; Muzakkir; Fikri; L, Sudirman; Aris (Universitas Islam Negeri Alauddin Makassar, 2024)
The controversy of passampo siri’ marriage in Bugis society and the determination of biological father from the perspectives of religious and traditional figures are discussed in Sidenreng Rappang Regency. Therefore, this research aims to understand the legal determination of passampo siri’ marriage and the establishment of biological father's status for child. Descriptive qualitative research uses primary data sources from community leaders, as well as traditional and religious figures through interviews and observations with an empirical sociological method. The results show that the reality of passampo siri’ in Sidenreng Rappang Regency is an alternative selected by parents for unmarried pregnant daughters disapproved of marrying the man responsible for preserving the family reputation. There is a divergence of opinions (ikhtilāf) among religious and traditional figures regarding the legal status of passampo siri’. Even though most informants agree that passampo siri’ is forbidden (harm) and invalid, some believe the concept is permissible and valid. The determination of child’s status does not differ according to the perspectives of religious and traditional figures in Sidenreng Rappang Regency. These groups assert that child born is not attributed to biological father.